IMPACT model training for Indian Council of Agricultural Research (ICAR) – Indian Agricultural Research Institute (IARI): Feedback survey report - Mishra, Abhijeet; Gabriel, Sherwin; Sulser, Timothy B.; Pal, Barun Deb (International Food Policy Research Institute, 2025)
A four-day training program (24-27 November 2025) on the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT), organized by the Division of Agricultural Economics, Indian Council of Agricultural Research (ICAR) - Indian Agricultural Research Institute (IARI), was designed to strengthen participants’ capacity in global agricultural modeling and scenario-based policy analysis. Through a comprehensive curriculum developed by International Food Policy Research Institute (IFPRI), the workshop provided both conceptual grounding and hands-on experience in using the IMPACT model and its network of linked modules, including climate, water, crop, and welfare models. Participants learned to design and run scenarios in GAMS and the IMPACT Excel Interface, interpret model results, and apply them to real-world questions in agricultural policy, climate change, and trade. The program emphasized the integration of biophysical and economic data for ex-ante policy analysis and equipped researchers to conduct multidimensional assessments of food security, technology adoption, and environmental sustainability.